2019
DOI: 10.1038/s41565-019-0500-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying error and leakage in an encoded Si/SiGe triple-dot qubit

Abstract: Quantum computation requires qubits that satisfy often-conflicting criteria, including scalable control and long-lasting coherence [1]. One approach to creating a suitable qubit is to operate in an encoded subspace of several physical qubits. Though such encoded qubits may be particularly susceptible to leakage out of their computational subspace, they can be insensitive to certain noise processes [2, 3] and can also allow logical control with a single type of entangling interaction [4] while maintaining fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 32 publications
6
90
0
Order By: Relevance
“…In particular we have shown that an exchange-only CNOT gate can be implemented with a computational speed comparable to or better than previous solutions, with good fidelity, provided the exchange interactions can be performed in parallel. The fidelities for these constructions exceed 0.99, which is comparable to fidelities demonstrated for one logical qubit in three quantum dots [10], and for two-qubit gates with other quantum devices [37][38][39]. Fidelities exceeding the conservative requirements for faulttolerance [40][41][42] can be achieved with a slow down of about a factor of two.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In particular we have shown that an exchange-only CNOT gate can be implemented with a computational speed comparable to or better than previous solutions, with good fidelity, provided the exchange interactions can be performed in parallel. The fidelities for these constructions exceed 0.99, which is comparable to fidelities demonstrated for one logical qubit in three quantum dots [10], and for two-qubit gates with other quantum devices [37][38][39]. Fidelities exceeding the conservative requirements for faulttolerance [40][41][42] can be achieved with a slow down of about a factor of two.…”
Section: Discussionmentioning
confidence: 67%
“…The best-known application of the 3DFS is to quantum computing with quantum dots where evolution under the exchange interaction can be more accessible than universal one-quantum-dot evolutions [3]. Indeed the requisite control over three quantum dots has been proven feasible by many experimental demonstrations [4][5][6][7][8][9][10]. The application to quantum dots is further supported by the ability to implement entangling logical gates between two blocks of physical spins carrying 3DFSs with exchange interactions only [3], but these gates require many steps and are often difficult to construct and understand from first principles (with a possible exception being [11]).…”
Section: Introductionmentioning
confidence: 99%
“…Qubit dephasing is another important consideration. We assume the dominant TQD dephasing channel for spin-photon coupling is electrical charge noise; magnetic noise (typically due to hyperfine gradients in Si/SiGe devices [5]) also causes dephasing and leakage but is mostly suppressed at the high values of J needed for spin-photon coupling. In circuit QED, the qubit dephasing rate is often parameterized as γ, which is well-defined for white noise channels but timescale-dependent for colored noise.…”
Section: Tqd Qubit Operation and Key Quantities For Spin-photon Couplingmentioning
confidence: 99%
“…Exchange can be used as the sole control mechanism for triple-quantum-dot (TQD) encoded qubits, which reside within a decoherence free subsystem (DFS) protected against global magnetic field fluctuations [2,3,4]. High-fidelity Si/SiGe TQD qubit operation has been shown experimentally [5], which is particularly relevant given the known physical (e.g., nuclearspin-free isotope) and technological (mature, scalable processing) advantages of silicon. However, transporting quantum information between distantly situated TQDs will require a mechanism different from exchange, due to the latter's intrinsically short-range nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation